Criminal Fines Issuing Tax Invoices Not Based on Actual Transactions with More than One Perpetrator - Sautma, Anggiat; suseno, Sigid Suseno; cahyadini, Amelia Cahyadini (JUSTISI, 2025)
Criminal fines in the case of issuance of tax invoices that are not based on actual transactions (TBTS) aim to recover losses of state revenue, but in the event that there is more than one perpetrator, the fines applied cannot be applied equally to each perpetrator because the fines applied become multiple. This writing is prepared to analyze the application of criminal fines for the issuance of TBTS tax invoices involving more than one perpetrator in the perspective of legal objectives. The research method used is normative legal research with a case study approach and a conceptual approach using the reference of Development Law Theory. This research is a new contribution to legal development in the application of criminal fines in the criminal offense of issuing TBTS tax invoices with more than one perpetrator. This writing concludes that the application of criminal fines in the case of issuance of TBTS tax invoices with more than one perpetrator is carried out proportionally and objectively according to the benefits or benefits obtained by each perpetrator in order to fulfill the principles of legal certainty, justice and expediency. The absence of rules regarding the mechanism for the application of criminal fines for the issuance of TBTS tax invoices with more than one perpetrator is an obstacle to efforts to apply criminal fines as a recovery for losses of state revenue.